Etude Des Determinants Socioeconomiques Et Techniques De La Psciculture Extensive En Cote D’ivoire - Amian, Atsé Franck; Wandan, Eboua Narcisse; Blé, Melecony Célestin; Vanga, Adja Ferdinand; Kaudhjis, Pierre Joseph Assi (European Scientific Journal, ESJ, 2017)
The contribution of fish farming is relatively low in the national consumption of fish products. Yet the country has a significant socio-natural potential, which well valued can reduce fish imports and enhance food security. This study, based on a survey conducted in the two main areas of extensive fish farming (Central West and Southwest), was to analyze the technical and socioeconomic determinants of family fish farming to support the dynamic development of this activity. The results showed that 98% of fish farmers are men of 51 to 60 years old. Most of them are illiterate practicing agriculture as their main activity. Farming infrastructure are usually composed of dams ponds (90%) of 0.25-1.5 ha, and ponds of 0.1 ha. Water was provided either by river (95%) or groundwater (5%). On average most farms are of mall size (3 ha) and were acquired by purchasing lands. Fish farmers mainly practiced mixed farming of Tilapia (Oreochromis niloticus) and Heterotis (Heterotis niloticus). In 60% of the cases, fish farming is associated with rice cultivation practiced in the shallows. Fish were mainly fed with rice bran. An important number of farmers (72%) practiced sexing of in order to improve their yields. Furthermore, 60% of them have a lower production to 6 tons per year, and fish were old between 1500 and 2000 CFA (1 FCFA=0,0014 euros) per kg leading to an average annual income of less than 5 million CFA francs.